2013
DOI: 10.1590/s2176-94512013000500008
|View full text |Cite
|
Sign up to set email alerts
|

Class II malocclusion treatment with the Herbst appliance in patients after the growth peak

Abstract: Based on the present results, it was concluded that the effects of treatment performed with the Herbst appliance in patients at post-peak stage of growth are predominantly of dentoalveolar nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…The treatment time was 2.79 (IQR=1.51) years for adults and 3.2 (IQR=1.5) and 4.1 (IQR=0.8) years for adolescents and children in mixed dentition, respectively. Treatment time seems shorter than the 48 months of treatment previously reported for adults treated with MPA (8), but greater than the 30 months described for adolescents treated with the Herbst appliance combined to fixed orthodontic appliances (23) or the 32 months from a pooled sample of children and adolescents treated with MPA associated to fixed orthodontic appliance (24). The longest treatment time in patients whose treatment started in the mixed dentition is probably related to a "waiting period" during the transition from mixed to permanent dentition.…”
Section: Discussionmentioning
confidence: 66%
“…The treatment time was 2.79 (IQR=1.51) years for adults and 3.2 (IQR=1.5) and 4.1 (IQR=0.8) years for adolescents and children in mixed dentition, respectively. Treatment time seems shorter than the 48 months of treatment previously reported for adults treated with MPA (8), but greater than the 30 months described for adolescents treated with the Herbst appliance combined to fixed orthodontic appliances (23) or the 32 months from a pooled sample of children and adolescents treated with MPA associated to fixed orthodontic appliance (24). The longest treatment time in patients whose treatment started in the mixed dentition is probably related to a "waiting period" during the transition from mixed to permanent dentition.…”
Section: Discussionmentioning
confidence: 66%
“…This increase was not statistically different between the groups. In previous studies, the range of the increase in the growth of the mandible in the late growth period was reported to be 1–4.15 mm following treatment with functional appliances [ 22 , 31 , 71 , 72 ]. Most researchers have found that craniofacial growth may extend to the late stages of growth and development in both males and females [ 73 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Herbst CBJ appliance design was described in detail in previously published article. 20 After removal of the Herbst CBJ appliance, the corrected anteroposterior relationship was retained with 3/16-inch Class II elastics as active retention for a mean period of 3 months. Patients were instructed to use 3/16-inch Class II elastics for 18 hours a day, removing it only for eating, brushing, and contact sports, and patient compliance was monitored monthly.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies to date have analyzed the treatment effects of the Herbst appliance after the growth peak, 19 20 21 and none of these studies have compared these effects with a comparable control group. The aim of the present study is to evaluate the effects of Class II malocclusion treatment with the Herbst Cantilever Bite Jumper (CBJ) appliance, combined with multibracket appliances after the growth peak at pretreatment.…”
Section: Introductionmentioning
confidence: 99%